Computational neuroscience : first Latin American Workshop, LAWCN 2017, Porto Alegre, Brazil, November 22-24, 2017, Proceedings /: first Latin American Workshop, LAWCN 2017, Porto Alegre, Brazil, November 22-24, 2017, Proceedings. (2017) - Unknown
No abstract available